A coupling scheme based on the partition of unity finite element method-finite element method for 3D vibro-acoustic problems. (September 2022) - Ma, Houbiao; Zhang, Yahui
Highlight: The coupling of non-matching meshes is realized by dividing virtual elements, implementing coordinate transformation. A novel efficient 3D vibro-acoustic analysis method PUFEM-FEM is developed. The PUFEM-FEM not only inherits the simplicity and good adaptability of the FEM-FEM, but also has better accuracy, efficiency and convergence. Abstract: The accuracy and efficiency of the finite element method-finite element method (FEM-FEM) for 3D vibro-acoustic problems degrade gradually with the increase of the excitation frequency due to the "dispersion error". In this study, a novel efficient 3D vibro-acoustic analysis method, the partition of unity finite element method-finite element method (PUFEM-FEM), is proposed based on the PUFEM applicable to acoustics and the FEM for thin plates, where the coupling of non-matching meshes is realized by dividing virtual elements, implementing coordinate transformation and introducing continuity conditions at the interface. The proposed method not only fully exploits the advantages of the PUFEM in suppressing "dispersion error" and reducing computational size, but also takes full use of its ability to analyze multiple frequencies without the need for repeated meshing, while retaining the FEM's ability to model the complex structures in great detail. Numerical examples demonstrate that the PUFEM-FEM has better accuracy, efficiency and convergence than the FEM-FEM for 3D vibro-acoustic problems.